Uppsala Biobank—the development of a biobank organization in a local, regional, and national setting - Anna Beskow (Upsala Journal of Medical Sciences, 2019)
A biobank is generally in an international setting considered as a sample collection with linked data. In Sweden we have a lot of sample collections, but the definition of a biobank has changed, and it has become an organization that administrates many sample collections as well as an infrastructure to support research. Uppsala Biobank was started in September 2008 as a joint biobank organization between Uppsala County Council and Uppsala University. At the start there were 138 registered biobanks in Uppsala for these two principals. The decision was to have only one biobank, where all previous biobanks would be transformed to be sample collections. Uppsala Biobank has gone from the wish to centralize biobanking administration to be a research infrastructure, a national model for hospital-integrated biobanking, a support structure for biobanking activities in the health care region, and the local competence center for all biobank issues in Uppsala.